2017
DOI: 10.4314/ahs.v17i2.22
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-126 and its potential function in coronary artery disease

Abstract: Objective: This study aimed to explore the role of miR-126 in coronary artery disease (CAD) patients and the potential gene targets of miR-126 in atherosclerosis. Methodology: A total of 60 CAD patients and 25 healthy control subjects were recruited in this study. Among the 60 CAD patients, 18 cases were diagnosed of stable angina pectoris (SAP), 20 were diagnosed of unstable angina pectoris (UAP) and 22 were diagnosed of acute myocardial infarction (AMI). Plasma miR-126 levels from both groups of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…Placental miR-16 expression predicts the risk of being born SGA [26] and miR-16-5p is down-regulated in IUGR pregnancies [43]. MiR-126 expression is down-regulated in patients with coronary artery disease [44] and 5. (a and b).…”
Section: Discussionmentioning
confidence: 99%
“…Placental miR-16 expression predicts the risk of being born SGA [26] and miR-16-5p is down-regulated in IUGR pregnancies [43]. MiR-126 expression is down-regulated in patients with coronary artery disease [44] and 5. (a and b).…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that this calcineurin/NFAT pathway is activated after oxidative stress stimuli [157,158]. In the in vivo experiments, inhibition of miRNA-199b caused normalization of the expression of Dyrk1a, a reduction of nuclear NFAT activity, and inhibition of hypertrophy and fibrosis in mouse models of heart failure [101,159]. Changed expressions of miRNA-1, -214, -29b, -342, -7, -107, -126, -125, -122, -423-5p, -320a, -650, -1228, -662, -583, -3175, -21, -22, and -92b have been shown in other studies of heart failure [106,152,156,[160][161][162][163].…”
Section: Heart Failurementioning
confidence: 99%
“…Other studies have also reported that circulating miR-19a, miR-29a, miR-30e, miR-145, miR-150, miR-155, miR-181d, miR-342, miR-378 and miR-484 levels are decreased in patients with stable CAD [152] and has been associated with subclinical atherosclerosis [152]. CAD severity was found to be inversely associated with circulating miR-126 levels [153]. Studies in patients with acute myocardial infarction (AMI) have identified several miRNAs which have the potential to act as predictive biomarkers.…”
Section: Circulating Mirnas As Potential Clinical Biomarkers For Athementioning
confidence: 86%